178k views
1 vote
-7(2 + 2x) = -84 pls try and show work

User Ru
by
5.0k points

2 Answers

5 votes

Answer:


\displaystyle \rm \longmapsto \: - 7(2 + 2x) = - 84


\displaystyle \rm \longmapsto \: - 14 + 14x = - 84


\displaystyle \rm \longmapsto \:14x = - 84 + ( - 14)


\displaystyle \rm \longmapsto \:14x =-70


\displaystyle \rm \longmapsto \:x = ( - 70)/(14)


\displaystyle \rm \longmapsto \:x = 5

  • For checking:


\displaystyle \rm \longmapsto \: - 7(2 + 2x) = - 84

  • Put x as 5:


\displaystyle \rm \longmapsto \: - 7(2 + 2(5) = - 84


\displaystyle \rm \longmapsto \: - 7(2 + 10) = - 84


\displaystyle \rm \longmapsto \: - 14 + ( - 70) = - 84


\displaystyle \rm \longmapsto \: - 84 = - 84

User Washington Guedes
by
5.3k points
2 votes

Answer:

The final answer is
\bold{x = 5}.

Explanation:

Hey there! We will solve this using the distributive property.

  • The distributive property states that when we are given
    a(b \pm c), we can "distribute" the a through the parentheses and therefore multiply together a & b as well as a & c.
  • This would end up giving us an equation such as
    (a * b \pm b * c).
  • After we get this, we can simplify it as a one-step, two-step, or multi-step equation.

Now, we can apply these methods and solve for x in the equation!


\text{-7(2 + 2x) = -84 \ \ This is where we begin distributing.}\\\\\text{To distribute, we will multiply the -7 by 2, and the - 7 by 2x.}\\\\\text{Be sure to keep the original operator in the parentheses!}\\\\\text{-14 - 14x = -84 \ \ Now, simplify the equation as a two-step equation.}\\\\\text{-14x = -70 \ \ Now, we have to divide by -14 on both sides to get x by itself.}\\\\\text{x = 5 \ \ And, now, we have our final answer!}

And there we go! We found that the final answer is 5. Hope this helps!

User Justin Geeslin
by
5.0k points